DIGITALISASI UMKM SEBAGAI KATALIS PEMULIHAN EKONOMI: INOVASI UMKM DI DESA WANASABA LOR, CIREBON - Lathifaturahmah (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2024)
This research focuses on digital transformation and national economic recovery through the digitalization of MSMEs as part of the national food security chain policy. The study was conducted in MSMEs in Wanasaba Lor and Wanasaba Kidul Villages, Talun Sub-district, Cirebon District. Using a qualitative descriptive approach, the study found that the digitalization of MSMEs can strengthen national and family economic resilience. However, the study also identified several challenges faced by MSMEs, including the quality of human resources, business management, access to information, capital, production capacity, technology support, and market access. To overcome these challenges, the study recommends several strategic measures such as mentoring of business activities, expansion of access to credit, participation in exhibitions, and HR training. The novelty of this research lies in its holistic approach in understanding and addressing the challenges faced by MSMEs in the digital era, including digital technology exploration, multi-sector collaboration, community-based approach, socio-economic impact evaluation, and business model innovation.